Effect of treatment with humic acid and benzyl adenine on the growth and productivity of strawberry (Damascus University Journal of agriculture sciences, 2024)
The experiment was carried out at Abi- Jarash farm - Faculty of Agricultural /Damascus University during season 2020 and 2021. In order to study the effect of two concentrations of humic acid (4 ml and 2 ml) and two concentrations of benzyl adenine (1000 PPM and 2000 PPM) and the interaction between the two factors on some morphological, physiological and fruits characteristics of the strawberry cv. Festival. The experiment was designed as randomized complete block design .The results showed that spraying with humic acid (HA) and benzyl adenine (BA) has a positive effect in improving the morphological and physiological characteristics of strawberry plants, in addition to an improvement in the qualitative characteristics of strawberry fruits. The number of leaves (23.2 leaf/plant), the number of runners(4.6runner/plant), the content of leaves from chlorophyll b (0.18mg/g wet weight), the weight, length and diameter of fruit (21.27 g, 3.717 cm, 2.943 cm, respectively). However, the treatment with humic acid (2ml) and benzyl adenine (1000 ppm) increased the leaves content of chlorophyll a and carotenoids (0.33 and 0.50 mg/g wet weight, respectively), while the (4 ml) humic acid treatment increased the plant height (31.63 cm). While the treatment with humic acid (4 ml) and benzyl adenine (2000 ppm) was superior to the rest of the treatments and the control in increasing the nitrogen, phosphorous and potassium content (1.33, 0.50 and 1.8%, respectively).
Keywords: strawberry; humic; benzyladenine; Growth; Productivity